Perlindungan Hukum terhadap Anak Perempuan sebagai Korban Tindak Pidana Perdagangan Manusia - Rani Kusuma Wardani; Levina Yustitianingtyas (Perspektif Hukum, 2021)
The development and advancement of information technology, communication, and transportation in the era of globalization is very rapidly developing, while in line with the development of crime mode, one of the crimes of globalization is the crime of human trafficking against girls today. This study uses normative juridical approach methods, as well as secondary data collected from primary materials, in the form of legal provisions, and their implementation; while secondary legal material is done in the form of literature studies that are then processed and analyzed qualitatively, making it easier for authors to analyze. Often girls become victims of trafficking crimes because of the factors behind the occurrence of trafficking crimes. Therefore, special protection for girls is required, namely the Law of the Republic of Indonesia No. 21 of 2014 on Child Protection, as well as a special Law to protect against people trafficking crimes, namely the Law of the Republic of Indonesia Number 21 of 2007 on the Eradication of People Trafficking, and the Law of the Republic of Indonesia Number 39 of 1999 on Human Rights